ผลของการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วมต่อพฤติกรรม และการมีส่วนร่วมในการป้องกัน และควบคุมโรคหนอนพยาธิของอาสาสมัครสาธารณสุขประจำหมู่บ้าน : กรณีศึกษาตำบลนางแล อำเภอเมือง จังหวัดเชียงราย - เรือนคำ, วัชรพงษ์ (Area Based Development Research Journal, 2014)
การวิจัยนี้เป็นการผสมผสานของการวิจัยเชิงสำรวจ และการปรับใช้วิธีการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วม (PAR: Participatory Action Research) โดยมีวัตถุประสงค์เพื่อศึกษาผลของการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วมต่อพฤติกรรมและการมีส่วนร่วมในการป้องกันและควบคุมโรคหนอนพยาธิของอาสาสมัครสาธารณสุขประจำหมู่บ้าน ในตำ บลนางแล อำเภอเมือง จังหวัดเชียงราย จำนวน 263 คน เก็บข้อมูลโดยใช้แบบสอบถาม การสนทนากลุ่มการประชุม และวิเคราะห์ข้อมูลโดยใช้ความถี่ ร้อยละ และเปรียบเทียบความแตกต่างคะแนนเฉลี่ยพฤติกรรมและการมีส่วนร่วมก่อนและหลังการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วม ผลการศึกษา บริบทก่อนการดำเนินการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วมพบการติดเชื้อหนอนพยาธิ 31 คน (ร้อยละ 11.8) พฤติกรรม ส่วนใหญ่อยู่ในระดับดี (ร้อยละ 71.1) การมีส่วนร่วมอยู่ในระดับดี (ร้อยละ 52.1) จากนั้นดำเนินการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วมซึ่งประกอบด้วย 1) การใช้วิธีถกปัญหาแลกเปลี่ยนเรียนรู้ร่วมกันในการวิเคราะห์ปัญหาและหาแนวทางแก้ไข 2) การใช้วิธีกระตุ้นให้ชาวบ้านมีบทบาทหลักในการร่วมจัดทำแผนงานโครงการและการจัดการ 3) การดำเนินกิจกรรมตามแผน ซึ่งประกอบด้วย การอบรมให้ความรู้เรื่องหนอนพยาธิ พฤติกรรมเสี่ยงต่อการติดเชื้อหนอนพยาธิและการอภิปรายบทบาทของ อสม. ต่อการป้องกันและควบคุมโรคหนอนพยาธิ และ 4) การติดตามและประเมินผลการปฏิบัติงาน ภายหลังการดำเนินการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วมพบว่า การติดเชื้อหนอนพยาธิลดลงจากก่อนการวิจัยเหลือเพียง 2 ราย (ร้อยละ 0.8) โดยพบเกิดการติดเชื้อใหม่ 2 ราย ไม่พบการติดเชื้อซ้ำในผู้ที่ติดเชื้อรายเดิม และพบว่าภายหลังดำเนินการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วมพฤติกรรมและการมีส่วนร่วมในการป้องกันและควบคุมโรคหนอนพยาธิเพิ่มมากขึ้น The Effects of Participatory Action Research to Behavior and Participatory of Helmintic Infection Prevention and Control of Village Health Volunteer : Nanglae Sub-district, Muang District, Chiang Rai Province This research is a combination survey research and deployment of participatory action research (PAR) aims to study the effects of participatory action research to behavior and participatory of helmintic infection prevention and control of village health volunteer, Nanglae sub-district, Muang district, Chiang Rai province. Study population was 263 village health volunteers. Data were collected by questionnaire, focus group, and meeting. The data was analyzed by frequency and percentage. Different mean was used to analyze the behavior and participatory levels both before and after used the participatory action research. The results of the context situation before used the participatory action research showed that a prevalence rate of helminthes infection was 11.8 . Most of the village health volunteers in Nanglae sub-district had the level of behavior was in good level (71.1 ) and the level of participatory was in good level (55.9 ). Then, the participatory action research was used, which includes: 1) discussion and learning together to analyze problems and find solutions 2) encouraging participants to design project plans and management 3) the implementation of planned activities. Which include provide training about helmintic infection, risk behaviors, and discuss the role of village health volunteers in prevention and control of helmintic infection, and 4) monitoring and evaluation After the participatory action research, revealed that the prevalence of helmintic infection reduced to 0.8 percent. All infectious cases were found as new infection cases and no recurrent case. This research found that the behavior and the participatiory of the prevention and control of helmintic infection were increasing.